Adolescent Sexual and Reproductive Health in El Salvador - Cortez, Rafael; Revuelta, Karin-Annabela; Guirola, Yolanda (World Bank, Washington, DC, 2016)
The aim of the study is to understand the sexual and reproductive health (SRH) behavior and determinants among adolescents in El Salvador using data from a survey of 1,258 adolescents’ aged 10-19 and 12 interviews with representatives from the Ministry of Health (MOH), Ministry of Education (MOE), nongovernmental organizations (NGOs), and United Nation (UN) agencies. The study found that adolescents were not educated enough on their sexual and reproductive health rights (SRHR), and have limited use of and access to contraceptives. Alcohol and violence were found to be associated with risky sexual behavior, requiring a multisectoral response from the government and civil society. Adolescents need to receive earlier and more accurate information on their SRHR; and this information should be disseminated in a way that empowers adolescents to make responsible decisions about their sexual reproductive health. The MOE can play a vital role in informing adolescents in this area, and adjust these programs when necessary. Further, the role of parents is critical, as the study found that adolescents are not receiving adequate and enough SRHR information from their parents. In addition, the MOH needs to offer adolescent-friendly health services, which includes trained health personnel. Although adolescents stated that the maternal and child health programs offered were satisfactory and the government has made an effort at educating adolescents on human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS), both the promotion of contraceptive methods and monitoring adolescent SRHR remain as key challenges to be addressed by multisectoral interventions.